Treatment of HER2-Positive Breast Cancer with Brain Metastases Using Anlotinib and Trastuzumab Deruxtecan: A Case Report - Chen Y; Liu C; Wen X; Wang C; He J (Dove Medical Press, 2024)
Yuanping Chen,1 Chao Liu,1 Xinglin Wen,2 Chen Wang,1 Jing He1 1Department of Oncology, Ganzhou People's Hospital, The Affiliated Ganzhou Hospital of Nanchang University, Ganzhou, People's Republic of China; 2Department of Medical Image, Ganzhou People's Hospital, The Affiliated Ganzhou Hospital of Nanchang University, Ganzhou, People's Republic of ChinaCorrespondence: Jing He, Department of Oncology, Ganzhou People's Hospital, The Affiliated Ganzhou Hospital of Nanchang University, Ganzhou, 341000, People's Republic of China, Tel +86_15297720705, Email 382505721@qq.comAbstract: Breast cancer with brain metastasis accounts for the second largest number of brain metastases among solid malignancies. Despite advances in HER2-targeted therapy, 50% of patients with human epidermal growth factor receptor 2-positive (HER2+) breast cancer develop brain metastases and are associated with poor outcomes. In this article, we report the case of a patient with HER2+ metastatic breast cancer who developed brain metastases, despite experiencing a durable effect on extracranial metastases after treatment with trastuzumab and pertuzumab. The patient exhibited intracranial progression while receiving treatment with trastuzumab deruxtecan monotherapy after secondary brain radiotherapy and multiple lines of therapy with anti-HER2 agents, such as pyrotinib, lapatinib, tucatinib, and ado-trastuzumab emtansine. However, the administration of anlotinib (an antiangiogenesis medication) and trastuzumab deruxtecan resulted in intracranial and extracranial partial response and was linked to manageable side effects. The present case indicates that the combination of anlotinib and trastuzumab deruxtecan may be a promising treatment option for patients with HER2+ breast cancer with brain metastasis. Nevertheless, further studies are warranted to verify the present findings.Keywords: HER2 positive, breast cancer, brain metastases, anlotinib, trastuzumab deruxtecan